Exploring the nurse navigator role: A thematic analysis. (16th April 2020) - Byrne, Amy‐Louise; Hegney, Desley; Harvey, Clare; Baldwin, Adele; Willis, Eileen; Heard, David; Judd, Jenni; Palmer, Janine; Brown, Janie; Heritage, Brody; Thompson, Shona; Ferguson, Bridget
Abstract: Background: Patients with complex chronic conditions experience fragmentation of care, unnecessary hospitalization and reduced quality of life, with an increased incidence of poor health outcomes. Aim(s): The aim of this paper was to explore how nurse navigators manage client care. This was achieved through an examination of narratives provided by the nurse navigator that evaluated their scope of practice. Method(s): All nurse navigators employed by Queensland Health were invited to participate in a study evaluating the effectiveness of the service. Eighty‐four self‐reported vignettes were thematically analysed to understand the work from the nurses' perspectives. Results: Two themes emerged from the vignettes. Theme 1, the layers of complexity, is comprised of three sub‐themes: the complex patient, the complex system and patient outcomes. Theme 2, professional attributes, has two sub‐themes: person‐centred care and clinical excellence. Conclusion: Navigators innovatively integrate services and address the fragmented nature of the health system. They apply expert clinical and social skills, through consistent and robust communication, to meet the needs of those with multiple chronic conditions. Implications for nursing management: Results provide insight into the new role, illuminating the work they achieve, despite system complexities.